Asuhan Kebidanan Komprehensif pada Ny. S di RSIA Masyita - Indah Nirmala; Halida Thamrin; Linda Hardianti Saputri (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2026)
Comprehensive midwifery care or Continuity of Care is a health service that is provided comprehensively and continuously starting from pregnancy, labor, postpartum, newborns, to family planning. The goal of this care is to improve the quality of midwifery services by focusing on helping mothers give birth in the most minimal way possible, as well as monitoring the physical, psychological, spiritual, and social health of the mother and her family. The pregnancy process begins with the meeting of the egg and sperm cells in the uterus, followed by the process of nidation and implantation of the embryo, and develops until the fetus is ready to be born, the pregnancy lasts for 40 weeks. Mrs. S G3P2A0 with a gestation of 38-40 weeks, with vital signs within normal limits and the general condition of the mother is normal. Labor is the process of releasing a full-term baby from the uterus, followed by the release of the placenta and amniotic membranes from the mother's body through the birth canal, Mrs. S gave birth on January 22, 2025 at 20.50 WITA with the condition of the mother and baby in good condition. A newborn is a child aged between 0 and 28 days, this period is the period where the baby has the highest risk of death, Mrs. S was born spontaneously and immediately cried without any abnormalities with a weight of 2690 grams, a body length of 45 cm. The postpartum period is a recovery period that occurs after giving birth and lasts for 40 days, Mrs. S made 2 postpartum visits at Masyita Hospital and 1 home visit at Jl. Angkasa IV Hall 2 with the condition of the mother and baby in good condition and vital signs within normal limits. Family planning aims to help married couples regulate the spacing between pregnancies and prevent unwanted pregnancies, but Mrs. S is willing to use a 1-month injection of contraception. This case study was conducted on Mrs. S aged 30 years at Masyita Hospital, Makassar in 2025. Based on the case study, there was a gap in the stages of Antenatal Care Midwifery Care, Intranatal Care Midwifery Care, and Family Planning Midwifery Care compared to the theory, even though the mother and baby were in normal condition.